Pharmacokinetic and Pharmacodynamic integration of tilmicosin against Mycoplasma gallisepticum in the target infection site in chickens - Zhang, Nan; Zhou, Minghu; Yan, Xiu; Liu, Jinxin; Yuan, Sheng; Yang, Hong; Ding, Huanzhong; Zhang, Dexian; Bai, Yinshan (Frontiers in Veterinary Science, 2022)
Mycoplasma gallisepticum (M. gallisepticum) is a primary respiratory pathogen of poultry and causes significant economic losses to the poultry industry. There were no reported articles concerning the Pharmacokinetics/Pharmacodynamics (PK/PD) interactions of tilmicosin against M. gallisepticum in vivo. In the current study, we established an in vivo M. gallisepticum infection model and tilmicosin was administered orally to the M. gallisepticum-infected chickens by different dosage regimens. The concentration of tilmicosin in lung tissue was determined by high-pressure liquid chromatography/tandem mass spectrometry (HPLC–MS/MS), besides the counting of the viable colony of M. gallisepticum in lung tissue was also monitored dynamically to appraise the PK/PD interactions of tilmicosin against M. gallisepticum. We found that anti-mycoplasmal activity was concentration-dependent and mycoplasmacidal activity was observed at tilmicosin dosage >7.5 mg/kg. The PK/PD parameter of AUC/MIC (The area under the concentration–time curve divided by the minimal inhibitory concentration) correlated well with anti-mycoplasmal efficacy (R2 = 0.92). The ratios of AUC/MIC for 1 log10 and 3 log10 colony-forming units [CFU]/lung reductions were 300.02 and 6,950.15 h, respectively. These findings indicated that tilmicosin may be therapeutically effective in chickens to treat M. gallisepticum lung infections if administered at a dose of 9.12 mg/kg.